Main elements of current spine biomechanics research: model, installation and test data - Xu, Bide; Li, Gang; Sun, Xueheng; Yang, Simengge; Sun, Ran; Gong, Ying; Song, Mingzhi (Frontiers in Bioengineering and Biotechnology, 2025)
Biomechanical principles are crucial for spinal research, enabling precise analysis of spinal behavior under various conditions. Through quantitative analysis and simulation of mechanical information, spinal function can be optimized, posture improved, and injury risk reduced. However, current methodologies in spine biomechanics remain incomplete and challenging for researchers to apply effectively. This paper reviews recent advances in experimental models, loading methods, instrumentation, and test data used in spine biomechanics research, aiming to provide a reference for research design and future developments in the field. Two primary types of research objects are highlighted: measurement models and digital models. Common loading modes include dynamic, quasi-static, and static approaches. Various experimental setups, each with distinct characteristics, play essential roles in simulating motion and collecting data. The most frequently used biomechanical indicators are also discussed. In summary, this work redefines, categorizes, and synthesizes the typical research workflow in spinal biomechanics. It is foreseeable that more unified, accurate, and innovative studies will enhance the application of spinal biomechanics in rehabilitation, treatment, auxiliary materials, and clinical evaluation.